THE RELATIONSHIP BETWEEN OBESITY AND DIABETES - Usanov Quvonchbek Rasul o’g’li (TADQIQOTLAR, 2026)
Abstract: The prevalence of both conditions has risen dramatically over recent decades, largely driven by sedentary lifestyles, unhealthy dietary patterns, and urbanization. Numerous scientific studies have established a strong and complex relationship between obesity and the development of diabetes, making obesity one of the primary modifiable risk factors for this metabolic disorder. Obesity is characterized by excessive accumulation of body fat, which negatively affects metabolic processes in the body. One of the key mechanisms linking obesity to diabetes is insulin resistance. These biochemical changes impair the body’s ability to use insulin effectively, leading to elevated blood glucose levels. Furthermore, chronic low-grade inflammation associated with obesity plays a crucial role in disrupting insulin signaling pathways. The enlargement of fat cells and infiltration of immune cells into adipose tissue contribute to systemic inflammation, which exacerbates metabolic dysfunction. In conclusion, obesity and diabetes are closely interconnected conditions with shared risk factors and underlying mechanisms. Addressing obesity through lifestyle modifications, including balanced diet, regular physical activity, and behavioral changes, is crucial in preventing and managing diabetes. Public health interventions and increased awareness are vital to combat the growing epidemic of these diseases and improve overall population health.